Digital storytelling intervention to enhance social connections and participation for people with mild cognitive impairment: a research protocol - Zhu, Di; Al Mahmud, Abdullah; Liu, Wei (Frontiers in Psychiatry, 2023)
Introduction Interventions utilizing the principles of digital storytelling can improve cognitive ability by cultivating positive emotions and framing a new way to enhance social participation among people with mild cognitive impairment. However, existing research has understudied group-based storytelling, focusing instead on building individual stories and connections with family and friends. In response to this research gap, this paper proposes co-designing a digital storytelling intervention for people with Mild Cognitive Impairment (MCI) to enhance their social participation and build meaningful connections. Methods We will conduct two co-design workshops with people with MCI (n = 12), their caregivers (n = 4–12), and therapists (n = 5) in Beijing, China, to facilitate the co-development of the digital storytelling application. During the first workshop, we will utilize card sorting and voting to define potential facilitators of social participation, identifying the abilities people with MCI want to improve through storytelling. During the second workshop, we will build on these findings to facilitate people with MCI and their caregivers to visualize the interfaces. After reflexive thematic analysis of the co-design workshops, we will develop a digital storytelling application and test its usability and efficacy among people with MCI and therapists, respectively. A single-blinded field test will be conducted with 20 community-dwelling adults with MCI (Age: 65+). The testing will consist of an intervention group of 10 participants who use the co-designed digital storytelling intervention and a control group of 10 participants who will not use the co-designed intervention on the waiting list. The intervention period will extend over 7 weeks, with individual intervention sessions lasting 30 min. We will evaluate its efficacy in terms of social participation, social connectedness, self-efficacy, subjective sense of happiness, and user experience of people with MCI. Discussion This study will examine an innovative digital storytelling intervention to enhance social participation among people with MCI. This study is expected to advance the concept of community-centric social groups in social health service contexts by integrating technological solutions with the self-identified needs and lived experiences of people with MCI, increasing the motivation of people with MCI to cultivate social participation. Ethics and dissemination Swinburne University of Technology’s Human Research Ethics Committee gave ethics approval for this research (Approval Number: 20226525-11105; Date: 26/09/2022). Our findings shall be reported in peer-reviewed journal articles and at relevant conferences.